- #1

username12345

- 48

- 0

[tex]

\begin{flalign*}

\mathrm{if} & & y & = & & x^n \\

\mathrm{then} & & \frac{dy}{dx} & = & & nx^{n-1} \\

\mathrm{so if} & & y & = & & x^2 - x - 2 \\

\mathrm{then} & & \frac{dy}{dx} & = & & 2x - 1 \\

\end{flalign*}

[/tex]

I can't find how it ended up as [tex]2x - 1[/tex]. Here's is my attempt:

[tex]

\begin{flalign*}

y & = & & x^2 - x - 2 \\

\frac{dy}{dx} & = & & nx^{n-1} \\

& = & & 2x^{2-1} - 1x^{1-1} - 1(2)^{1-1} \\

& = & & 2x - 1 - 1 \\

& = & & 2x - 2 \\

\end{flalign*}

[/tex]

How do I get to the same result of [tex]2x - 1[/tex] ?